Effect of Coconut Water and Urea on Seedling of Palm Palm (Elaeis Gueneensis Jacq) in Pre-Nursery - Ulina C. Jenni Simatupang; Asmina Herawaty Sinaga; Hery Andi Sitompul (Jurnal Penelitian Pendidikan IPA, 2026)
This research aims to determine the effect of providing coconut water and urea to increase optimal growth of oil palm seedlings. This research was carried out on Medan community land in Amplas Village/Subdistrict, Percut Sei Tuan District. From April to June 2024. This research used a factorial randomized block design (CRD) consisting of 2 treatment factors with the symbol A consisting of 3 levels, namely; (A1) 300 ml/polybag (A2) 400 ml/polybag and (A3) 500 ml/polybag. The second factorial is with the symbol U which consists of 3 levels, namely; (U1) 1 g/polybag (U2) 1.82 g/polybag and (U3) 2 g/polybag. So that 9 treatments were obtained. Each treatment was repeated 3 times. The observation data was then carried out by analysis of variance using the F test at 5% level. If the difference was significant then the test was continued with the Duncan test. From the results of the research and discussions carried out, conclusions were obtained, including: 1). The coconut water treatment had no significant effect on plant height, number of leaves, leaf length and leaf area. And it has a real effect on the root volume of oil palm seedlings. 2). The application of urea dosage had a significant effect on the number of leaves, leaf length, leaf area and root volume. Good growth of oil palm seedlings according to the dosage in this research is 2g/polybag. 3). The interaction between giving coconut water and urea dosage did not have a significant effect on the growth of plant height, number of leaves, leaf length and leaf area of ​​oil palm seedlings.